Pediatric intradialytic hypotension: recommendations from the Pediatric Continuous Renal Replacement Therapy (PCRRT) Workgroup - Raina, Rupesh; Schaefer, Franz (Pediatric nephrology, 2019)
Intradialytic hypotension (IDH) is a common adverse event resulting in premature interruption of hemodialysis, and consequently, inadequate fluid and solute removal. IDH occurs in response to the reduction in blood volume during ultrafiltration and subsequent poor compensatory mechanisms due to abnormal cardiac function or autonomic or baroreceptor failure. Pediatric patients are inherently at risk for IDH due to the added difficulty of determining and attaining an accurate dry weight. While frequent blood pressure monitoring, dialysate sodium profiling, ultrafiltration-guided blood volume monitoring, dialysate cooling, hemodiafiltration, and intradialytic mannitol and midodrine have been used to prevent IDH, they have not been extensively studied in pediatric population. Lack of large-scale studies on IDH in children makes it difficult to develop evidence-based management guidelines. Here, we aim to review IDH preventative strategies in the pediatric population and outlay recommendations from the Pediatric Continuous Renal Replacement Therapy (PCRRT) Workgroup. Without strong evidence in the literature, our recommendations from the expert panel reflect expert opinion and serve as a valuable guide.
Gesehen am 04.04.2019